Critical community-engaged scholarship in an undergraduate food systems capstone: A case study from Public Health - Sipos, Yona; Ismach, Alan (Frontiers in Sustainable Food Systems, 2022)
In this perspective paper, we present a case study of food systems pedagogy and critical community-university engagement within a school of public health at a large and public research university. We start by providing a contextual foundation for the importance of intentionally centering equity-oriented curriculum and community partnerships in academic settings. After highlighting institutional mandates and curricular innovations from a food systems capstone course, we utilize key questions of critical community-engaged scholarship to analyze the case and critically reflect on gaps and opportunities for ongoing growth.